Políticas públicas de educação para os/as agricultores/as familiares : um diálogo entre a Fetraf-Sul/CUT e o estado - Tondin, Celso Francisco (2013)
The Brazilian family farming has received increasing attention, particularly from 2002 onwards, with the governments of the presidents Luiz Inácio Lula da Silva (PT) and Dilma Vana Rousseff, both the PT. The importance given to this sector resulted in the enactment of Law nº 11.326/2006 laying down guidelines for the formulation of the National Policy Family Farming and Rural Family Ventures, which predict that the planning and execution of public actions for this segment should match several areas, including education. This law was formulated with the participation of social movements, including the Federation of Workers in Family Agriculture Southern Region (Fetraf-Sul/CUT). In this context, take the education public policies as an object of study is a paramount importance for the state and Brazilian society and demonstrates the psychological science commitment to monitor, discuss and contribute to the policies development to citizenship, in this case a historically excluded segment, the/the farmers/the family. Thus, this thesis aims to identify the education concepts of public policies in force in this area and are aimed at farming families, identifying in which aspects the state and Fetraf-Sul/CUT concepts converge or diverge. For this, it seeks to describe and discuss how these actors (State and Fetraf-Sul/CUT) conceive such policies and how dialogue with each other, considering that families are produced by means of the proposals development in rural areas.The method used in this study was to documentary research, constituting its corpus current documents that were produced by these actors on the topic education. The information was processed from the Critical Discourse Analysis proposed by Fairclough with the conceptual contribution of Cultural Studies, the Schizoanalysis and the humanities studies constructs about the reality of the countryside, enabling the questioning of such policies as cultural practices that can be investigated from a cultural point of view and the task that they do subjectively. Accordingly, we found that the State Fetraf-Sul/CUT and State based on the premise that rural schools , which is linked to the urban model, does not meet the individuals needs and interests who live in the countryside, so there is a need a field school . The Fetraf-Sul/CUT, marked by ideological choice of socialism and class-union characteristics, sees education as training for political and trade union activities of/ the farmers/families in the struggles undertaken by the entity, intending to propagate a identity to be a the family farmer and be cutista and reverse the tendency of deletion of peasant culture. For its part, the state promulgates attend the needs not only of the countryside people, but also water and forests, calling them diversity of rural populations . Nevertheless, State and Fetraf-Sul/CUT agree that family farming is important for the construction of an alternative project to agribusiness, the sustainable development and solidarity project, agroecological base and territorial approach, although Fetraf-Sul/CUT explain clearly the issue of dispute over land while the state is limited to criticize capitalism without directly approaching the land question.Both actors preach that education should be liberating at the same time claiming that its goal is to be a priori to keep families in rural areas, stabilizing their identity. Therefore, we propose to think emancipation not as a cultural stability, but as a becoming establishes several possibilities. Thus, public policies could engage in, rather than just maintain these families in rural areas, befriend them transit from farm to city and town to the countryside, in other words, allow natural trajectories for each family and for each/a of their members